Histology of lung cancer: experience from a tertiary care centre in South India - S., Veni Krishna; J., Balachandran (International Journal of Research in Medical Sciences, 2019)
Background: Lung cancer is a leading cause of mortality worldwide and is increasing at an alarming rate in developing countries. Inspite of advances in treatment, prognosis of lung cancer is extremely poor. It is because of delayed presentation and difficulty in obtaining histological diagnosis. Histological confirmation is difficult in all cases due to the limited biopsy specimen obtained via bronchscopy / transthroacic biopsy. Primary objective was to study the histology of lung cancer at a tertiary care centre in South India. Secondary objective was to study association between smoking habit and histological type of lung cancer Methods: Cross sectional study conducted at Tertiary teaching hospital, South India in 100 patients with suspected lung cancer. Data on symptoms, smoking status, histological diagnosis were recorded using a structured questionnaire. Statistical analysis was done on the data collected. Chi square test was used to assess the statistical significance. Results: Total 100 lung cancer patients with histopathological diagnosis were included in the study. In the present study, histopathologically 90% of the patients had non-small cell lung cancer and 10% had small cell type of cancer. In male patients squamous cell carcinoma was the most common diagnosis, and majority were smokers. In female most common type was adenocarcinoma (40%). Conclusions: Adenocarcinoma (41.9%) was the commonest histological type in our study and this was the commonest histological type seen in females and nonsmokers.